Brain plasticity underlying acquisition of new organizational skills in children: A Rashomon analysis - Martinez Agulleiro, Luis; Deng, Bowen; Gallagher, Richard; Abikoff, Howard B.; Yoncheva, Yuliya; Robinson, Lauren; Conlon, Greta; Haroon, Maleeha; Yan, Chao-Gan; Di Martino, Adriana; Zhao, Yihong; Castellanos, F. Xavier (Frontiers in Neuroimaging, 2025)
ObjectiveWe used resting-state functional magnetic resonance imaging to identify changes in brain functional connectivity (FC) associated with Organizational Skills Training (OST).MethodIn an open, waitlist-controlled, randomized clinical trial (NCT04108273), 51 children aged 8–12 years with deficient organizational skills were assigned to immediate tele-health OST treatment (twice weekly, 10 weeks) or waitlist. We obtained Children’s Organizational Skills Scale-Parent version (COSS-P) scores and examined FC changes between dorsal anterior cingulate cortex (dACC) and preregistered subcortical anterior ventral striatum (aVS) regions-of-interest.ResultsOST produced significantly lower COSS-P scores compared to waitlist, with a large effect size (Cohen’s f2 = 0.77). Initial imaging analyses revealed a significant increase (instead of the predicted decrease) in FC between dACC and the aVS component of the default mode network in the immediate treatment group (ΔFC = 0.092 ± 0.041, 95% CI [0.009, 0.175], p < 0.05). Analyses were then performed with two additional analytic pipelines, neither of which detected any significant effects.ConclusionAlthough improvements in organizational deficits were associated with increased FC within a circuit linking dACC and the default mode network region of the aVS in one analysis, the direction was the opposite of predicted and results did not replicate. Thus, we highlight the tentativeness of our findings; we have de-identified all the data and made it available for investigators to examine and to combine with other datasets in mega- and meta-analyses. Future studies should also include alternative control conditions and larger samples.Clinical trial registrationhttps://clinicaltrials.gov/study/NCT04108273?cond=NCT04108273&rank=1.